Rice terrace as a support for sustainable mass tourism in the perspective of collaborative governance in Tegallalang tourism village Gianyar - Wijaya, Komang Adi Sastra; Artini, Ni Wayan Putu; Rahayu, Putu Yoga Darma; Dewi, Sang Ayu Nyoman Sinta; Riani, Ni Wayan (Tennessee Research International of Social Sciences, 2024)
Tegallalang Rice Terrace is the advantage and characteristic of Tegallalang village tourism. The potential of tourism villages can be an opportunity for local governments to increase Regional Original Income (PAD). When the tourism sector provides great benefits to the community, of course the community's pragmatic thinking is inevitable. The development of tourism support is increasingly massive in the rice terrace area, causing the phenomenon of conversion of agricultural land functions. In this case, the presence of the government is needed to prevent the phenomenon of land conversion and erosion of value through regulation. This study uses a qualitative research type with a descriptive approach combined with a collaborative governance perspective. This study shows that the existence of the Tegallalang rice terrace is in a development towards a sustainability crisis. However, the role of "customary elders" such as the initial initiators of the rice terrace is essential in maintaining a sustainable rice terrace through regulations agreed upon by both the western and eastern parties. From a collaborative governance perspective, management is decentralized from the local government by giving authority to local communities to fully manage the rice terrace. Although the private sector contributes to managing the view to attract tourists, their involvement is more commercial than collaborative. This condition reflects the potential for synergy that has not been optimally utilized between tourism object managers and the private sector to increase tourism appeal while maintaining environmental sustainability.